Social Presence Theory: Relevance for HRD/VHRD Research and Practice. Issue 3 (August 2019) - Bickle, Jason T.; Hirudayaraj, Malar; Doyle, Alaina
The Problem: Social presence theory (SPT) is the degree to which a person is perceived to be a "real person" in their computer-mediated communication or virtual environments. The level of social presence influences the quality of virtual interactions and outcomes. SPT has not been examined within human resource development (HRD) or virtual human resource development (VHRD); therefore, it is not known if increased social presence could improve virtual teams/organizations and online instruction. The Solution: Designing online environments and practices to increase social presence could enhance VHRD within virtual teams, online instructional design, and educational settings. Application of Community of Inquiry (CoI), Social Presence Model, and SPT-inspired instructional design through Gagne's nine events are discussed with recommendations to improve HRD/VHRD by fostering trust, communication, collaboration, personal relationships, and learning within virtual resources and teams. The Stakeholders: The literature and application of SPT would benefit HRD/VHRD researchers, HR practitioners, educators, and team leaders/managers.